Fixed Dose Combination of Ceftazidime Plus Tobramycin Acts as Free Radical Scavenger in Liver of Mus musculus Mice - Dwivedi, V. K.; Soni, A.; Chaudhary, M.; Sehgal, R.; Shrivastava, S. M. (Current Enzyme Inhibition, 2009)
Free radicals are causative factor for aminoglycoside induced tissue injury. Fixed dose combination therapy of ceftazidime plus tobramycin reduces liver toxicity than single therapy of tobramycin. The objective of present study was designed to determine the activity of antioxidant enzymes as well as some biochemical parameters along with MDA level by the administration of tobramycin and its fixed dose combination (FDC) with ceftazidime in liver of Mus musculus mice. Eighteen mice were selected and divided into three groups of six mice each. Control group was treated with normal saline and other groups were treated with tobramycin sulphate (4.0 mg/Kg body weight/ day) and FDC of ceftazidime plus tobramycin group (34.1 mg/Kg body weight/ day) for seven days treatment. Overnight fasting animals were sacrificed on 8th day and liver was taken out after perfusion and the Serum glutamic oxaloacetic transaminase (SGOT), Serum glutamic pyruvic transaminase (SGPT) and alkaline phosphatase as well as antioxidant enzymes along with MDA level in mice were determined. Our results showed that the antioxidant enzyme activities and alkaline phosphatase level were significantly decreased along with significant increase in the SGOT, SGPT and MDA levels in tobramycin sulphate treated group as compared to control group. But in case of fixed dose combination of ceftazidime and tobramycin (tobarcef) treated group, all enzymes activities and levels were found to be significantly improved as compared to tobramycin alone treated group. These findings indicate that a fixed dose combination of ceftazidime + tobramycin prevents liver toxicity by improving the level of MDA, liver enzymes and antioxidant activities, due to induction of tobramycin drug.
Keywords: MDA